The structural transition of the production system: Regional policy in common understanding - Carl Devos (European Regional Science Association (ERSA), 1998)
Several scientists, politicians are perceiving a fundamental shift in the structure of the production process and the political regulation-system governing that process. Others claim that there?s nothing worth mentioning about this rage, and posit the continuation of long known cyclical and secular trends. There is a general lack of common understanding and accurate definition in the debate among and between politicians and academics. Neither the concept of ?globalisation? nor that of ?regionalisation? seems to be an accurate ?description? nor an ?explanation? of the structural transformations of the European economy. Yet these vague nominations do have real implications for the perception and situation-definition of the mass and their leaders. Using theoretical tools as the ?Rule of Anticipated Reactions?, ?Hidden Faces of Power?, ?non-decision-making? etc., the proposition is that the ?invisible hands? of market-law and (supra-)state policies have altered the bargaining positions of ?states? and organisations favouring business. The debate about the ?retreat? or ?withering away? of the state, vs. scientists pleading to ?bring the state back in? the analysis, is noticeable in most countries. But the ?objective data? used is unsuitable: they cannot measure accurately the transition under research. The current discussion cannot reveal the importance of the concept of ?structural power? in social relationships: the shifting balance of power between states and markets and between labour and capital. Because of the current division of social sciences, individual disciplines cannot capture thoroughly the transition of the economic system. This transition consists of the shift away from a ?Fordist Regulation? towards ?Something Else?. This transition has farreaching consequences for the neo-corporatist organisation of the ?European? economies and the underlying social differentiation. It is endangering the necessary social cohesion and hindering the supple functioning of the labour market. The classic ?European? Keynesian Welfare State, is undergoing strong incentives, perhaps dictates, towards drastic adjustment. The conditions imposed by mobile capital, both financial and productive, are narrowing the policy-options of national and regional governments: the decrease of difference. At least, this is what is proclaimed in popular discours, in contrast to different findings of scientific research. The modern version of ?beggar-they-neighbour?, the competitive provision of investment-incentives, the involuntarily condescending attitude towards the captains of industry ... are disciplining the labour-force and leading to unemployment and poverty. Because of the delegation of important parts of the socio-economical policy-domains towards the regional government, these too are forced to play the game. Intra-Union and even intra-state social dumping, sometimes for the sake of the European subsidy-policy, are complicating an ?regional understanding?. How can the regions answer this common threat without resulting in a ?mutually assured destruction?? How can they counter these ?structural adjustment plans? without a suitable adequate institutional apparatus on the Union level? What is known in political geography as the ?jumping of scales? is changing the relationship between different policy-levels. The ?regional question? at the turn of the Century is a difficult one: how can the regions defy the obligations of the global production system without rendering a community of regions impossible before it is constructed.
Keywords: 330